2013
DOI: 10.1002/adfm.201300760
|View full text |Cite
|
Sign up to set email alerts
|

Photosensor Device Based on Few‐Layered WS2 Films

Abstract: Few‐layered films of WS2, synthesized by chemical vapor deposition on quartz, are successfully used as light sensors. The film samples are structurally characterized by Raman spectroscopy, atomic force microscopy, scanning electron microscopy, and high‐resolution transmission electron microscopy. The produced samples consist of few layered sheets possessing up to 10 layers. UV–visible absorbance spectra reveals absorption peaks at energies of 1.95 and 2.33 eV, consistent with the A and B excitons characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
440
9
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(479 citation statements)
references
References 31 publications
27
440
9
3
Order By: Relevance
“…The same device structure has also been used in conjunction with other 2D semiconductors, such as GaSe, GaTe, In 2 Se 3 , black phosphorus and several others [46][47][48][49][50][51][52]. Wavelength-dependent studies have shown that the photocurrent follows the TMD absorption spectrum.…”
Section: Photodetectorsmentioning
confidence: 99%
“…The same device structure has also been used in conjunction with other 2D semiconductors, such as GaSe, GaTe, In 2 Se 3 , black phosphorus and several others [46][47][48][49][50][51][52]. Wavelength-dependent studies have shown that the photocurrent follows the TMD absorption spectrum.…”
Section: Photodetectorsmentioning
confidence: 99%
“…Indeed, similar lattice parameters allow the creation of a variety of TMDC heterostructures with very few structural defects [26]. However, despite their technological relevance [27] and various results from first principles calculations [28][29][30], the properties that can be expected from such systems are still under debate. In particular, the nature of the band gap (direct versus indirect) of the MoSe 2 -WSe 2 and MoTe 2 -WTe 2 heterostructures is not settled [31].…”
Section: Introductionmentioning
confidence: 99%
“…Although graphene offers the possibility of photodetection over an unrivaled wavelength range [3][4][5] and with ultra-high bandwidth 5,6 , its photoresponsivity is limited by the vanishing bandgap and picosecond carrier lifetime. Recently, TMDs have attracted much interest for photodetection applications [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , due to their potential for achieving very high responsivities. Broadly speaking, two groups of TMD-based photodetectors have been investigated: (i) vertically stacked heterostructure devices, where a few-layer TMD semiconductor is sandwiched between graphene or transparent metal electrodes 11,12 , and (ii) lateral metal-TMD-metal detectors [13][14][15][16][17][18][19][20][21][22][23][24] , whose device structure resembles that of field-effect transistors [27][28][29] (FETs).…”
mentioning
confidence: 99%